An empirical study on effectively managing Buyer Supplier Relationship: A case of Indian Automobile Industry - Singh, Parmjot; Kalra, Deepshikha (International Journal of Psychosocial Rehabilitation, 2020)
The automobile sector is flourishing at a very fast pace but in a very sophisticated way. The firms are looking outwards for improving sales, increasing margins, to have a competitive edge over competitors and global recognisation. The above goals can only be achieved if the relationships between buyer and supplier firms could be managed effectively. Thus, the present study investigates the significant dimensions of buyer supplier relationships in Indian automobile sector and to investigate the impact of these dimensions on the robustness of these relationships. Researcher has collected data from 676 employees from buyer and supplier firms to examine the degree of relationship between channel partners. The existing literature suggests that information sharing, commitment, trust and collaborative behavior of partners are the vital elements in nurturing successful relationships between partners thus a conceptualized hypothesized model is formulated which is further confirmed with the help of second order confirmatory factor analysis. The research work proposed that information sharing, collaboration and commitment has the highest contribution in transforming the higher degree of relationships. Buyer supplier relationships deteriorate rapidly in the absence of elements of information sharing, collaboration and commitment dimensions.